2022
DOI: 10.3390/coatings12101422
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic SiO2/Trimethylchlorosilane Coating for Self-Cleaning Application of Construction Materials

Abstract: This study has demonstrated, for the first time, the potential application of coatings to protect bricks or architectures against detrimental atmospheric effects via a self-cleaning approach. In this research, a facile fabrication method was developed to produce amorphous SiO2 particles and their hierarchical structures via applying trimethylchlorosilane (TMCS). They were fully characterized by various surface analytic tools, including a goniometer, SEM, AFM, zeta sizer, and a spectroscopic technique (FTIR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…The band gap of unmodified ZnO NRs, ZnO(SA1), ZnO(SA2), and ZnO(SA3) is 3.31 eV, 3.29 eV, 3.27 eV, and 3.26 eV respectively. There is no appreciable change in band gap of ZnO NRs after surface modification with stearic acid [78] . This suggests that the light response (absorption) is not changed much on going from unmodified ZnO NRs to stearic acid modified ZnO NRs.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The band gap of unmodified ZnO NRs, ZnO(SA1), ZnO(SA2), and ZnO(SA3) is 3.31 eV, 3.29 eV, 3.27 eV, and 3.26 eV respectively. There is no appreciable change in band gap of ZnO NRs after surface modification with stearic acid [78] . This suggests that the light response (absorption) is not changed much on going from unmodified ZnO NRs to stearic acid modified ZnO NRs.…”
Section: Resultsmentioning
confidence: 92%
“…This indicates better self‐cleaning property of SA modified ZnO NRs compared to unmodified ZnO NRs. A comparison of different surface modification methods of metal oxide nanoparticles used for self‐cleaning is given in Table S2 [72–78] . It can be noted that the present surface modification method requires less time (5 minutes), no heating and economical.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building walls are exposed to the air, and the surfaces are washed by rainwater, which makes the walls prone to peeling and cracking. At the same time, organic and inorganic contaminants can easily adhere to the surface of building walls and accumulate to produce black spots, which affect the aesthetics of the walls [2,3]. It was found that the humidity and cleanliness of the walls are closely related to environmental health [4], and it is urgent to improve the hydrophobicity and cleanliness of building wall surfaces [5].…”
Section: Introductionmentioning
confidence: 99%